2014
DOI: 10.1038/ng.2915
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in SLC30A8 protect against type 2 diabetes

Abstract: Loss-of-function mutations protective against human disease provide in vivo validation of therapeutic targets1,2,3, yet none are described for type 2 diabetes (T2D). Through sequencing or genotyping ~150,000 individuals across five ethnicities, we identified 12 rare protein-truncating variants in SLC30A8, which encodes an islet zinc transporter (ZnT8)4 and harbors a common variant (p.Trp325Arg) associated with T2D risk, glucose, and proinsulin levels5–7. Collectively, protein-truncating variant carriers had 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
380
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 445 publications
(396 citation statements)
references
References 27 publications
14
380
1
1
Order By: Relevance
“…Among the variants, the two most common sequences failed to express a stable protein. Thus, SLC30A8 haploinsufficiency leading to a lower expression of the transporter appears from these studies to protect against T2D [73].…”
Section: Znt8 and T2d: Gwas Studiesmentioning
confidence: 80%
See 2 more Smart Citations
“…Among the variants, the two most common sequences failed to express a stable protein. Thus, SLC30A8 haploinsufficiency leading to a lower expression of the transporter appears from these studies to protect against T2D [73].…”
Section: Znt8 and T2d: Gwas Studiesmentioning
confidence: 80%
“…These findings thus uncovered a more complex role for ZnT8 in glucose homeostasis, and in particular in tissue-tissue interactions, than previously thought. Importantly, these complex interactions might contribute to the differences in the impact of genetic deletion of ZnT8 in mice versus reduction in levels (by 50 %) in rare allele carriers [73] or inheritance of risk variants (R325W) [77].…”
Section: Znt8 Studies In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…As is the case in other analytic settings, the use of phenotypic extremes tends to lead to an overestimate of the effect of the variant and tends to overestimate the proportion of functionally active variants in a region, both of which support the value of population-based samples. 34 However, much larger sample sizes will be needed in order to have the power to detect associations in these instances.…”
Section: Discussionmentioning
confidence: 99%
“…Examples from T2D research highlight the diverse routes by which human genetics can inform translational medicine: (1) the combination of common-variant GWASs and candidate-gene resequencing has demonstrated that loss-of-function mutations in SLC30A8 (MIM: 611145; encoding a zinc transporter expressed in pancreatic islets) are protective for T2D, leading to efforts by several pharma companies to develop ZnT-8 antagonists; 93 (2) the use of genetic variants as instruments that ''simulate'' variation in environmental and biochemical exposures has clarified the extent to which vitamin D intake, early nutrition, circulating lipid levels, and chronic inflammation play causal roles with respect to the development of T2D [94][95][96][97][98] and has defined the relationship between insulin resistance and the distribution of adipose tissue; 99 (3) the identification of genetic variants associated with individual variation in response to commonly used therapeutic agents has refined our understanding of the mechanisms through which those agents operate 100,101 and, in some instances, has led to therapeutic optimization on the basis of genetic and/or clinical phenotype; 102 and (4) the combination of -omic measurements, longitudinal clinical phenotypes, and GWAS data has highlighted sets of molecules (e.g., branched-chain amino acids) that not only are prospectively associated with T2D progression but could also play a causal role in T2D development and thereby provide valuable clinical tools for stratification and prognostication. 103,104 Auto-immune Diseases Variant and Gene Discovery.…”
Section: Type 2 Diabetesmentioning
confidence: 99%